External Integration and Halal Assurance System Integrity for Achieving the Performance: Based on The Structural Contingency Theory Approach - Meldona; Sulis Rochayatun (PT FORMOSA CENDEKIA GLOBAL, 2024)
Based on the Structural Contingency Theory, which examines external and internal factors influencing business strategies within the extent of the Halal Food Supply Chain (HFSC), the role of the Halal Assurance System as a variable that can mediate the influence of supplier, customer integration and regulator integration on the Halal MSMEs’ performance. This study used 195 of samples Halal MSME proprietors in Malang Regency with a quantitative methodology, with data evaluated by SEM-PLS. The study’s findings prove that supplier and customer integration have an impact to the MSMEs’ performance. However, regulator integration only significantly impacts MSME performance. The Halal Assurance System owned by halal MSMEs can mediate the influence between supplier and customer integration on the performance of MSMEs. However, the Halal Assurance System owned by halal MSMEs does not significantly mediate the influence of the integration of regulators on the MSMEs’ performance. Effective supplier and customer integration management yields advantages that enhance performance via the Halal Assurance System